Lymph node dissection in atypical endometrial hyperplasia - Taskin, Salih; Kan, Ozgur; Dai, Omer; Taskin, Elif A.; Koyuncu, Kazibe; Alkilic, Aysegul; Gungor, Mete; Ortac, Firat (GALENOS YAYINCILIK, 2017)
Objective: The rate of concomitant endometrial carcinoma in patients with atypical endometrial hyperplasia is high. We aimed to investigate the role of lymphadenectomy in deciding adjuvant treatment in patients with concomitant atypical endometrial hyperplasia and endometrial carcinoma. Material and Methods: Women with atypical endometrial hyperplasia were enrolled in this retrospective study. Lymph node dissection was performed in only some patients who gave informed consent if their surgeon elected to do so, or if the intraoperative findings necessitated. The final histopathologic evaluations of surgical specimens were compared with endometrial biopsy results. Results: Eighty eligible patients were evaluated. Seventy-two (90\%) patients had complex hyperplasia with atypia, and 8 (10\%) patients had simple hyperplasia with atypia. Hysterectomy and bilateral salpingo-oophorectomy were performed to all patients

37 also underwent lymph node dissection. Lymph node dissection was extended to the paraaortic region in 9 of 37 patients. The concomitant endometrial carcinoma rate was 50\%. Two patients had lymph node metastasis. Among 40 cases of carcinoma, 17 had deep myometrial invasion and/or cervical or ovarian involvement or grade 2 tumors with superficial myometrial invasion on hysterectomy specimens

27.5\% of all carcinomas were stage Ib or higher. Conclusion: The concomitant endometrial carcinoma rate was high in patients with atypical endometrial hyperplasia. Nearly half of these patients had risk factors for extrauterine spread. Lymph node dissection might be helpful to decide adjuvant treatment.
Keywords: Atypical hyperplasia; concomitant; endometrial carcinoma; lymphadenectomy